2020
DOI: 10.1039/d0ra01532f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alkali and transition metal-doped TiO2 hole blocking layers on the perovskite solar cells obtained by a two-step sequential deposition method in air and under vacuum

Abstract: Planar perovskite solar cells (PPSCs) have received great attention in recent years due to their intriguing properties, which make them a good choice for photovoltaic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The gas‐phase assisted solution method has outstanding performance in the preparation and precise composition control of large‐area devices. [ 65 ] Yim et al [ 66 ] used MAPbCl 3 vapor to treat PbI 2 films for controlling the stoichiometric ratio of film elements. A similar method has also been adopted by Mohammadi et al [ 67 ] on the PbCl 2 –PbI 2 mixed lead inorganic film.…”
Section: Methods and Reaction Principlementioning
confidence: 99%
“…The gas‐phase assisted solution method has outstanding performance in the preparation and precise composition control of large‐area devices. [ 65 ] Yim et al [ 66 ] used MAPbCl 3 vapor to treat PbI 2 films for controlling the stoichiometric ratio of film elements. A similar method has also been adopted by Mohammadi et al [ 67 ] on the PbCl 2 –PbI 2 mixed lead inorganic film.…”
Section: Methods and Reaction Principlementioning
confidence: 99%
“…The ETL plays an important role in extracting electrons from the perovskite layer. It can prevent contact between the fluorine-doped SnO 2 (FTO) and perovskite layer to avoid the recombination of electrons and holes, and reduce energy loss at the interface [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally known that charge recombination is highly responsible for reducing the energy conversion efficiency of PSCs. Many researchers have focused on the ETL of PSCs [16,17,27]. Some investigators have tried to add a new layer into the ETL to form a bilayer, which has been demonstrated as an effective way to modify the interfacial behavior and photovoltaic performance of PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…[140][141][142] However, the large offset between the valence band of halide perovskites and the working potential of the metal electrode significantly reduces the hole extraction efficiency, detrimental to the PV performance. [143,144] The offset can be overcome either via depositing a double-layer transparent conducting oxide (TCO) for enhanced charge separation [145][146][147] or by doping the halide perovskite to realign the energy band. [108,144,148] The current highest-recorded PCE for HTL-free PSCs (PCE: %20%) was achieved by energy band realignment through p-type doping of the perovskite.…”
Section: Device Architecturementioning
confidence: 99%